The impact of wingate and progressive tests on homocysteine, vitamin b6, b12 and folic acid levels in athletes' blood - Murawska-Cialowicz, E. (Central European Journal of Sport Sciences and Medicine, 2014)
Homocysteine is an indirect metabolite of methionine metabolism, as well as of creatinine, and it plays an important role in many biochemical processes. Physical effort modifies homocysteine concentration in the blood, as well as the substances taking part in its metabolism. The aim of the study was to assess the influence of intensive efforts of diverse energy changes on the concentrations of homocysteine and the vitamins involved in its metabolism - vit. B6, vit. B12 and folic acid. In the study athletes performed Wingate and progressive test. Before and after tests homocysteine, vitamins B6, B12 and folic acid and creatinine were assayed. Concentration of homocysteine, vit. B12 and creatinine in the blood increased after both tests. Concentration of vit. B6 decreased and folic acid increased after Wingate test while they did not change after a progressive test. Homocysteine concentration negatively correlated with folic acid but positively with creatinine concentration in the blood, as well as with LBM. Regardless of its duration and energetic changes, intensive effort leads to an increase in homocysteine concentration. Correlation of homocysteine with creatinine and the LBM suggest that people with bigger muscle mass can have higher homocysteine concentration in the blood.